The Effect of Time Scarcity Promotion, Shopping Motives and E-WoM on Impulse Buying Behavior of Shopee Consumers in Manado City - Ahmad, Yavi N.; Mandey, Silvya L.; Pandowo, Merinda HC (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This study aims to identify and analyze the effect of Time Scarcity Promotion, Hedonic Shopping Motives, Utilitarian Shopping Motives and E-WoM on Impulse Buying behavior. The number of samples in this study was 100 respondents, collecting data using a questionnaire. The quantitative analysis method used is validity, reliability, classical assumptions and multiple regression using the SPSS 25 application. Shopee is an E-Commerce platform that offers a variety of attractive programs to attract more consumers. Along with the progress of E-Commerce, Impulse Buying behavior in society has developed. The results of the study show that simultaneously Time Scarcity Promotion, Hedonic Shopping Motives, Utilitarian Shopping Motives and E-WoM have a positive and significant effect on Impulse Buying behavior. Then partially each variable Time Scarcity Promotion, Hedonic Shopping Motives, Utilitarian Shopping Motives has a positive and significant effect on Impulse Buying behavior, while E-WoM partially has a positive and insignificant effect.